Case Report: Hyponatremia Secondary to Desmopressin Administration Prior to Percutaneous Kidney Biopsy: A Case-Based Review - Vornicu, Alexandra; Obrişcă, Bogdan; Cotruta, Bogdan; Dulămea, Adriana Octaviana; Caceaune, Nicu; Ismail, Gener (Frontiers in Medicine, 2021)
Bleeding remains the most clinically relevant complication of kidney biopsy and several prophylactic approaches were proposed, including desmopressin administration. We present the case of a 60-year-old man with a history of liver transplantation, admitted for the evaluation of a renal dysfunction. As part of our department protocol, desmopressin 60 μg was administered orally, 2 h before the percutaneous kidney biopsy. The patient developed acute, severe, symptomatic hyponatremia (i.e., headache and recurrent vomiting), followed by a life-threatening upper gastrointestinal bleeding due to a Mallory-Weiss syndrome. Although it is often used as bleeding prophylaxis prior to kidney biopsy, data regarding the efficacy and safety of desmopressin in this setting are inconsistent. Accordingly, we performed a thorough literature review of the use of desmopressin as bleeding prophylaxis prior to kidney biopsy, focusing on the incidence of hyponatremia. The reported incidence of hyponatremia (<130 mmol/l) was 7–11%, probably because serum sodium was monitored in few studies. Nevertheless, hyponatremia was rarely symptomatic but, in some cases, like the one presented here, its complications could be severe. Pre-biopsy low serum sodium and estimated glomerular filtration rate as well as high spot urine sodium and non-restricted fluid intake were reported to be associated with hyponatremia incidence. However, the current evidence cannot clearly establish which patients benefit the most from desmopressin use with respect to bleeding complications. We propose that when desmopressin is used for bleeding prophylaxis prior to kidney biopsy, measurements of serum sodium levels, before and every 6 h after, should complement ultrasound and hemoglobin as part of the patient post-procedural monitoring. Also, water intake should be restricted in the day of biopsy. However, this proposed approach should be adequately evaluated in a clinical trial.